Economics of Eucalyptus Plantations Under Agro-Forestry - Mathur, R. S.; Sharma, K. K.; Ansari, M. Y. (Indian Forester, 1984)
Increasing attention is being paid to raising large leale plentations of Eucalyptus spp under Agro-Forestry throughout India to meet the demand for fore firewood, small timber, poles, beams, pape, pulp etc. A shift in the cropping pattern from agriculture to farm forestry has been experienced in the States of Uttar Pradesh, Punjab and Haryana. Eucalyptus has been planted by the formers on field bunds, along field boundaries, in roilS along water channels and in compact blocks in agriculture fields with variable spacings. The present paper presents the results in respect of economic reasibility or Eucalyptus raised with or without agrlculture on fields bunds and in blocks at varying spacings viz. 2.5 m×2.5 m, 3.0 m×1.5 m, 4.0 m×2.0 m and 6.0 m × 1.0 m on farm lands. Cultivation of Eucalyptus at wider spacing in combination with agriculture crops at 8 years rotation ensures high economic returns.